Sistem Pemantau Gas di Tempat Pembuangan Sampah Akhir Berbasis Internet of Things - Fathur Zaini Rachman (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2018)
This research developed a gas monitoring system in the final waste disposal. The system has implemented the Internet of Things (IoT) using the ESP8266 Wi-Fi module to transmit methane (CH4) and carbon dioxide (CO2) data concentration, as well as temperature and humidity to the ThingSpeak server. Users can monitor and access these environmental data through social media Twitter and websites from anywhere. The fastest data delivery can be obtained with a time interval of 16 seconds on each data packet sent when there is an Internet connection.